THE EFFECTS OF LAVENDER ESSENTIAL OIL AND GALLIC ACID PRE-TREATMENT ON THE NEUROCOGNITIVE ASSESSMENT OF POST-STROKE WISTAR RATS - FELLA, CHEBBAH; AMINA, DJOUINI; LATIFA, AIDAOUI; NARIMENE, LAHMANES; CHAHIRA, RETEM; CHAIMA, SMILI; ABDELMADJID, BAIRI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Stroke is a multifactorial, fatal and often disabling neurodegenerative disease in which neurons are degenerated leading to cognitive and muscular problems, there is no curative treatment for this disease; the drugs available on the market offer symptomatic relief with some improvement of daily functions. Thus, phytochemicals with multifactorial efficacy may be promising substances for the treatment of cerebral ischemia and its recurrences that would have been prevented by various plants and plant products. The aim of our study is to evaluate the effect of lavender oil and gallic acid administered orally at doses of 200 mg/kg and 100 mg/kg, respectively, prior to stroke induction by middle cerebral artery occlusion in Wistar rats. The aim is to evaluate their effects on post-stroke sequelae, such as anxiety, exploration and memory (spatial and working), which were quantified and compared between: the control, non- pretreated stroke and pretreated stroke batches. The results indicate a better cognitive-motor recovery on an anxious and exploratory level in the rats pretreated with GA and LEO, while memory capacities are superior in the latter compared to the non-pretreated stroke group. These findings reveal and support the neuroprotective effect of gallic acid and lavender essential oil taken separately or in combination.